Communication in a disordered world - Simon, S; Moustakas, A; Stoytchev, M; Safar, H (2001)
The effect of scattering on the information transfer rate for cell phones and wireless microwave communication devices was analyzed. The antennas in the array measures the relative phase and amplitude of the signal arriving from the particular source and then transmits with the same relative amplitude but with opposite phase. It is found that the scattering instead of decreasing the efficiency, increases the information transfer rate for wireless communication devices.